History by HBO : televising the American past - Weeks, Rebecca (The University Press of Kentucky, 2022)
"The television industry is changing, and with it, the small screen's potential to engage in debate and present valuable representations of American history. Founded in 1972, HBO has been at the forefront of these changes, leading the way for many network, cable, and streaming services into the "post-network" era. Despite this, most scholarship has been dedicated to analyzing historical feature films and documentary films, leaving TV and the long-form drama hungry for coverage. In History by HBO: Televising the American Past, Rebecca Weeks fills the gap in this area of media studies and defends the historiographic power of long-form dramas. By focusing on this change and its effects, History by HBO outlines how history is crafted on television and the diverse forms it can take. Weeks examines the capabilities of the long-form serial for engaging with historical stories, insisting that the shift away from the network model and toward narrowcasting has enabled challenging histories to thrive in home settings. As an examination of HBO's unique structure for producing quality historical dramas, Weeks provides four case studies of HBO series set during different periods of United States history: Band of Brothers (2001), Deadwood (2004-2007), Boardwalk Empire (2012-2014), and Treme (2010-2013). In each case, HBO's lack of advertiser influence, commitment to creative freedom, and generous budgets continue to draw and retain talent who want to tell historical stories. Balancing historical and film theories in her assessment of the roles of mise-en-scène, characterization, narrative complexity, and sound in the production of effective historical dramas, Weeks' evaluation acts as an ode to the most recent Golden Age of TV, as well as a critical look at the relationship between entertainment media and collective memory"--